Rehabilitation interventions for glioma patients: a mini-review - Spina, Stefania; Facciorusso, Salvatore; Cinone, Nicoletta; Pellegrino, Raffaello; Fiore, Pietro; Santamato, Andrea (Frontiers in Surgery, 2023)
Glioma is a group of tumors that originate from glial cells within the central nervous system and comprise 27% of all tumors and 80% of malignant tumors. With remarkable progress in surgical practices, chemotherapy, and radiation therapy, patients with glioma are experiencing greater survival times, which means they need more rehabilitative care. In fact, people with this condition may experience a variety of symptoms that can affect their functions and drastically reduce their quality of life. In fact, patients suffering from glioma has a distinctive symptom complex highlighting the requirement for customized care. Growing evidence shows that rehabilitation therapy can improve the functional prognosis and quality of life of glioma patients. However, there is limited evidence of the success of rehabilitation protocols designed specifically for individuals with glioma. It is essential to determine the most comprehensive rehabilitation programs as well as the sufficient resources, dosage, and duration. The goal of this mini-review was to classify and map rehabilitation interventions used to treat multiple disabling sequalae in individuals affected by glioma. We aim to provide a comprehensive overview of the rehabilitation protocols used for this population, so that clinicians have a guide to support treatment and an inspiration for further research. This document is intended to be a reference point for professionals involved in the management of adult patients with gliomas. Further exploration is needed to form improved care models for recognizing and addressing functional restrictions in this population.